Strategic management in the global economy (New York : John Wiley and Sons, 1997)
This book is about: Global firms and the global environment; The globalization process; Competitive analysis and strategic planning: The corporate view; ...
Keywords: Economics; Business; Management; Strategic planning; Enterprises; International business enterprises -- Management; International business enterprises -- Planning; Strategic planning; International economic relations